2009
DOI: 10.1590/s0021-75572009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Priapismo em crianças: revisão de fisiopatologia e tratamento

Abstract: A new physiopathologic theory concerning sickle cell disease, which questions the traditional vascular blockage mechanisms by deformed red cells and proposes that endothelial inflammatory activation is the main cause of clinical problems, allows to propose new therapeutic maneuvers to solve sickle cell priapism. The absence of good quality evidence to treat sickle cell priapism suggests the necessity to conduct good prospective multicenter protocols to investigate the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Because the median age of the patients studied was 24 years and because of the significant relationship between the occurrence of priapism and older age, it might not be surprising that sexual arousal/ intercourse has been noted in previous studies to be of aetiological importance [ 13 , 16 ]. It is noteworthy that studies have shown that the incidence tends to plateau as patients approach 30 years of age and beyond [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the median age of the patients studied was 24 years and because of the significant relationship between the occurrence of priapism and older age, it might not be surprising that sexual arousal/ intercourse has been noted in previous studies to be of aetiological importance [ 13 , 16 ]. It is noteworthy that studies have shown that the incidence tends to plateau as patients approach 30 years of age and beyond [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed lack of an association with platelet counts and Hb concentration may be partly explained by the fact that transfusion and drugs like hydroxycarbamide (aimed at increasing the Hb concentration and reducing the platelet count) have not been very effective in the treatment or prophylaxis of this condition [ 13 , 19 ]. This is evidenced both by clinical experience and by the report by Adeyoju et al [ 13 ], which showed that analgesia, rehydration and possibly exchange blood transfusion were the preferred treatment modalities amongst physicians [ 13 , 16 , 20 ]. However, exchange blood transfusion, aimed at reducing the HbS percentage as well as improving haematocrit levels, does not usually yield satisfactory results [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leg ulcers are the most frequent cutaneous manifestation of SCD, which may contribute to morbidity, with an incidence of 25% to 75% among affected patients [ 9 , 10 ]. Priapism is one of the less well characterized complications of the SCD disorder [ 11 ], with a prevalence of 2–6% in paediatric sickle-cell clinics [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…3, 8 Interestingly, we found that there was a significant decline in the number of admissions for SCD-related priapism (0.8% to 0.4%, p<0.001 for trend), but not for the number of individual patients diagnosed with SCD-related priapism (~2% throughout the study period, p=0.34 for trend). Rates of priapism diagnoses and admissions in males with SCD varied widely among PHIS hospitals.…”
Section: Discussionmentioning
confidence: 67%